2012
DOI: 10.1109/tpel.2011.2115256
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Nine-Switch Power Conditioner for Power Quality Enhancement and Voltage Sag Mitigation

Abstract: A nine-switch power converter having two sets of output terminals was recently proposed in place of the traditional back-to-back power converter that uses 12 switches in total. The nine-switch converter has already been proven to have certain advantages, in addition to its component saving topological feature. Despite these advantages, the nine-switch converter has so far found limited applications due to its many perceived performance tradeoffs like requiring an oversized dc-link capacitor, limited amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(61 citation statements)
references
References 30 publications
0
60
0
Order By: Relevance
“…The sum of the active power from the gird source, SC and PC is given by (16) which is just about the active power consumed by the loads. …”
Section: B Grid Voltage Sag Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The sum of the active power from the gird source, SC and PC is given by (16) which is just about the active power consumed by the loads. …”
Section: B Grid Voltage Sag Analysismentioning
confidence: 99%
“…Ignoring the power losses of the converters and lines, the SC capacity and the PC capacity can be obtained by (17) and (18) according to (6), (9) and (16). (19) Selecting a suitable angle  can optimize the capacity allocation of the SC and PC to realize a high economic benefit, a low investment cost and a small equipment capacity.…”
Section: Upqc Coordinated Control Optimization Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, several studies have been reported in the literature employing reduced switch count converters in different areas [5][6][7][8][9][10][11][12][13]. The reduced switch count has been employed in unified power quality conditioner (UPQC) using only ten switches in [5] and using nine-switches in [8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on slightly different topological principles, a more recent example can be found almost simultaneously in [5] and [6], where the nine-switch converter is proposed to save three switches. The nine-switch converter has since been tested for single and dual motor drives [5] [7], uninterruptable power supplies [6] and unified power quality conditioners [8] with its performance noted to be not always satisfactory for some of them [7]. This is no doubt linked to performance constraints introduced by its reduced switch count, which are also experienced by other reduced-switch topologies.…”
Section: Introductionmentioning
confidence: 99%